Current status of laparoscopic transhiatal esophagectomy for esophageal cancer patients: a systematic review of the literature. Issue 1 (21st December 2016) - Parry, K.; Ruurda, J. P.; van der Sluis, P. C.; van Hillegersberg, R.
SUMMARY: Minimally invasive techniques in transhiatal esophagectomy (THE) were introduced to reduce morbidity and enhance postoperative recovery. Aim of this study was to systematically review the current status and possible beneficial effects of the minimally invasive approach in THE. A systematic search was performed in PubMed, the Cochrane Library, and Embase to identify English articles published on laparoscopic THE. Comparative cohort studies were included for critical appraisal. Data describing perioperative and oncological outcomes were analyzed. A total of four comparative cohort studies that compared laparoscopic THE ( n  = 122) with open THE ( n  = 144) and four noncomparative cohort studies reporting on laparoscopic THE ( n  = 212) were included in this review. Median blood loss was significantly lower in the laparoscopic group in all studies (100–500 vs. 526–900 mL). Length of hospital stay was also significantly shorter for the laparoscopic approach in all studies (9–13 vs. 12–16 days). One study reported less major postoperative complications after laparoscopic THE (12 vs. 23%), in the other studies no differences were found. Also no differences were found with regard to operating time, postoperative morbidity, radicality, and lymph node retrieval. Based on these pioneer studies, laparoscopic THE was demonstrated to be safe and feasible with evidence of reduced blood loss and shorter hospital stays. However, level 1 evidence is lacking and further research is warranted to confirm these findings and also to evaluate long-term oncologic outcomes.